Administrative and Legal Regulation of the Functioning of the State Bureau of Investigation - Kozar, Maksym (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The administrative and legal bases of activity of the State Bureau of Investigations are investigated. An important role in determining the principles of combating corruption in Ukraine is played by administrative and legal regulation, given that acts of administrative legislation establish the organizational and managerial foundations of anti-corruption activities of authorized entities, regulate administrative and legal relations arising in this area.The absence of a unifed legal consolidation of the term «administrative and legal regulation of the functioning of the State Bureau of Investigation» has been established and its author’s defnition has been proposed. The main precondition for the establishment of the State Bureau of Investigation is the state’s commitment to effectively reform the judiciary and law enforcement agencies in accordance with European standards, including through the establishment of new institutions, in accordance with the Strategy for Reforming the Judiciary and Related Legal Institutions for 2015-2020.The system of international legal acts related to the activities of the State Bureau of Investigation is analyzed, which consists of: 1) those that establish guarantees of human and civil rights and freedoms in the exercise of powers by law enforcement agencies, including the State Bureau of Investigation; 2) those that set requirements for the main activities of law enforcement agencies, including the State Bureau of Investigation; 3) those that determine the most relevant activities of law enforcement agencies, including the State Bureau of Investigation.Attention is drawn to the content of key laws and regulations in the feld of exercising the powers of the State Bureau of Investigation. The main legal act of the legislative level is the Law of Ukraine «On the State Bureau of Investigation», which establishes the basic principles of organization and activity, guarantees of independence, tasks, powers, structure and number, fnancial and logistical support of the State Bureau of Investigation, social and legal protection. and the responsibility of its employees, as well as the interaction of the State Bureau of Investigation with other government agencies. Bylaws additionally regulate certain aspects of the State Bureau of Investigation, including: principles of establishing the State Bureau of Investigation as a central executive body, tasks of the Public Oversight Board at the State Bureau of Investigation as a collegial advisory body, principles, directions, conditions, organization conducting psychophysiological research using a polygraph at the State Bureau of Investigation.